Analysis of Lead (Pb) and Zinc (Zn) Levels in Milkfish (Chanos Chanos) at Kalanganyar Market Sidoarjo Using Atomic Absorption Spectrophotometer (Aas) Method: Uji Kadar Timbal (Pb) dan Seng (Zn) pada Ikan Bandeng (Chanos chanos) di Pasar Kalanganyar Sidoarjo dengan Metode Atomic Absorption Spectrophotometer (AAS) - Hanum, Galuh Ratmana; Wahyudi, David Andrian; Pramushinta, Intan Ayu Kusuma (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Water pollution occurs due to the inclusion of chemical substances, components in the form of gases, and solvents so that the quality of water becomes polluted and harmful to the life of organisms in the waters, especially in fish farming. Polluted waters can contain heavy metals. fish can be exposed to heavy metals due to polluted waters. Heavy metals with high or low levels can also cause various types of dead water biota. If the fish exposed to heavy metals consumed by humans will over-accumulate or accumulate in the body, thus endangering health. This study was conducted to determine the levels of heavy metals Lead (Pb) and Zinc (Zn) contained in the meat of fish bandeng in the market Kalanganyar Sidoarjo with Atomic Absorption Spectrophotometer (AAS). This research was conducted in Applied Chemistry Laboratory of Medical Laboratory of Faculty of Health Sciences, University of Muhammadiyah Sidoarjo and Chemistry Laboratory of FMIPA Universitas Islam Maulana Malik Ibrahim Malang in February-April 2021. In this study using descriptive cross sectional research type. Data analysis method using measurement and observation as well as descriptive statistical analysis. 20 samples were used. The results of heavy metal levels in this study obtained the highest levels of lead heavy metal (Pb) of 0.354 mg/kg. While the lowest level is 0.062 mg/kg. Zinc (Zn) heavy metal content is highest at 3,132 mg/kg. While the lowest level is 0.606 mg/kg.